KAJIAN YURIDIS ANGGOTA KEPOLISIAN DAERAH BENGKULU SEBAGAI PENASEHAT HUKUM DALAM KASUS TINDAK PIDANA NARKOTIKA DI PENGADILAN NEGERI KELAS I A KOTA BENGKULU (Fakultas Hukum Dehasen, 2019)
The implementation of Perkapolri number 7 year 2015 is the provision of legal aid by members of police as legal advisor and make advocacy against a criminal act of drugs in the Council of District court class 1 A Bengkulu was contradictive with the regulation of lawyer number 18 year 2003 and number 12 year 2001 about Hierarchy of legislation. That contradictive was happen very significant between opinion of the judge in the council of district Bengkulu, Opinion of persecutor in judicial and opinion of lawyer. The judge said that base on PP number 3 year 2003 members of police have authority to defend the criminal act of another members of POLRI who did a criminal act. The Persecutor and lawyer have same opinion that existence members of police contradictive with regulation of lawyer number 18 year 2003 and constitution 1945. This research is intended to analyze legal basic authority members of police to be a legal advisor to suspect/defendant who are members of the POLRI. This research is judicial empirical legal research. The main data in this research is primary data, furthermore also supported by secondary data through library research. After the data was collected, it was processed qualitative descriptively so the result showed that a legal advisor for suspect who are members of POLRI only a lawyer in accordance with regulation of lawyer number 18 year 2003 about avocado and contradictive with regulation of lawyer number 12 year 2001 about hierarchy of legislation. Keywords : members of police, legal advisor, criminal act, council of district cout